Entrepreneurial Marketing for Enhancing Competitiveness in the Beef Cattle Industry among Smallholder Farmers - I Putu Gede Didik Widiarta; Cori Qamara; Alina Azzara; Muhammad Fahrul; Rahmat Budi Ramadhani (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2025)
The beef cattle industry plays a vital role in rural economies, especially among smallholder farmers, who face numerous challenges in accessing markets, reducing production costs, and competing with larger, industrial-scale producers. This study examines the role of entrepreneurial marketing (EM) in enhancing the competitiveness of smallholder beef cattle farmers. The study aims to identify the entrepreneurial marketing strategies employed by smallholders to overcome barriers to market access and enhance their profitability and sustainability. Using a systematic literature review (SLR) methodology, this paper synthesises findings from various studies published between 2019 and 2024 to explore how smallholder farmers implement innovative strategies, such as digital marketing, product differentiation, and the development of value propositions, to gain a competitive edge. The results show that digital marketing plays a crucial role in expanding market reach, while product differentiation, particularly through sustainable practices and ethical production, enables smallholders to command premium prices. Cooperative marketing networks provide an effective means for overcoming logistical barriers and accessing larger markets. The study concludes that policy support is essential in fostering an environment conducive to the adoption of entrepreneurial marketing practices, particularly through digital literacy programs and subsidies for sustainable farming practices. The findings offer actionable insights for policymakers, industry stakeholders, and smallholder farmers to promote the sustainability and growth of the smallholder beef cattle sector.